ANALYSIS OF PLATELET COUNT ON FIBROSIS DEGREE IN CHRONIC HEPATITIS B PATIENTS - Hairul Anwar; Mutmainnah Mutmainnah; Ibrahim Abdul Samad (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Chronic hepatitis B is an infectious liver disease caused by hepatitis B virus that persist for more than 6 months. Fibrosis is a result of fibrogenesis which is the formation of connective tissue (scarring) caused by liver tissue damage. Liver damage will affect the production of thrombopoetin causing disturbances in the balance between destruction and production of platelet resulting in decreased platelet counts. This study was a retrospective cross-sectional study by taking the data from medical records of chronic hepatitis B patients who were tested for complete blood count and fibroScan at the Dr.Wahidin Sudirohusodo Hospital Makassar from January 2014 to July 2016. The result showed a total of 323 chronic B hepatitis patients, 99 with severe fibrosis, 84 with moderate fibrosis and 140 with mild fibrosis. The Spearman correlation test showed a significant correlation between the platelet count and the degree of fibrosis (p <0.001) and showed a positive correlation between both of them with a very strong correlation (r = 0.802). The Kruskal-Wallis test showed a significant difference between platelet count and the degree of fibrosis (p<0.001). The conclusion is that a decreased platelet count is a sign of an increase in the degree of fibrosis in chronic hepatitis B patients. It is suggested to perform another study with larger samples based on the degree of fibrosis.